Habeas data e efetividade do direito fundamental à autodeterminação informativa - Guardia, Karina Joelma Bacciotti Selingardi (2022)
Nowadays, the legal experience, boosted by globalization and technological advances, recognizes new risks to the essential rights of human beings. The threat of vitrification or transparency of the human being by the collection and abusive or fraudulent use of personal data, which in the recent past was related to state act, currently extends to private and public entities, national and transnationals. The reality imposes not only to create but also to revisit the protection norms, seeking effective ways to deal with the potentialized threats by the use of informatics. Upon considering the Habeas Data as the object of investigation, the study reveals wider norms content than the previously defended subjective right to constitutional act, directly contributing to the effectiveness of the informational self-determination right. By making use of the dogmatic work method, which is common in every legal research, being consistent in doctrinal, legislative, and jurisprudential analyses, the work embodies questions such as the incorporation of human rights canons in the catalog of fundamental rights; the concepts of subjective rights and guarantees; the development of the informational self-determination right; the introduction of Habeas Data on the 1988 Constitution, and the partial comprehension of its content in the doctrinal and jurisprudential frame, proposing at the end a vitalizing interpretation from the objective dimension of the fundamental rights. In its objective dimension, Habeas Data expresses the principle that determines to the State the protection duty of personal data against third parties interventions – a duty that conjugated to the principle of the dignity of the human being and the right of privacy, bases the existence of the fundamental right to the self-determination informational in the Brazilian legal frame. The objective dimension inherent from the Habeas Data allows the updating of the constitutional action, broadening not only the passive pole to cover private entities, but also the hypothesis of the writ's place, aiming to strengthen the plexus of guarantees provided by the General Data Protection Law (Law nº 13.709/2018), contributing to the effectiveness of the protection of personal data